2017
DOI: 10.1590/abd1806-4841.20176015
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous conjunctival melanoma and lentigo maligna melanoma

Abstract: Lentigo maligna has an extensive and neoplastic character. It typically progresses slowly and may eventually develop into an invasive melanoma, which is called lentigo maligna melanoma. Ocular melanoma is the second most common type of melanoma. The uvea is the most common site of origin of ocular melanomas, while conjunctival melanoma accounts for about 1-5% of cases. In this article, we describe a rare case of synchronic conjunctival melanoma and lentigo maligna on the face.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Ocular melanoma is the second most common type of melanoma and is often observed as an eye neoplasm. Lentigo maligna might eventually develop into invasive melanoma ( 64 ). “Melancholia,” “Melanosis,” and “Melasma” might have similar spellings as melanoma and hence confuse the searchers.…”
Section: Discussionmentioning
confidence: 99%
“…Ocular melanoma is the second most common type of melanoma and is often observed as an eye neoplasm. Lentigo maligna might eventually develop into invasive melanoma ( 64 ). “Melancholia,” “Melanosis,” and “Melasma” might have similar spellings as melanoma and hence confuse the searchers.…”
Section: Discussionmentioning
confidence: 99%
“…Shields et al have also observed that melanomas showed significant features of increased thickness compared to other pigmented lesions of the conjunctiva (24). However, the comparison of melanoma with pigmented naevus of the conjunctiva, showed that melanomas are most often only partly elevated (part of the lesion is flat and part is nodular), which is most probably related to their likely formation on the foundation of PAM (5,10,11).…”
Section: Discussionmentioning
confidence: 99%
“…). The mortality rate is between 13-40% over ten years (8,9,11,15). Local tumour recurrence has been reported in 50-70% of patients (4,5,12,16).…”
mentioning
confidence: 99%
“…of all ocular melanomas (2,3). The incidence of CMM has significantly increased in the USA and Europe over the recent years.…”
mentioning
confidence: 99%